2013
DOI: 10.4103/2230-8210.109714
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid disorders in polycystic ovarian syndrome subjects: A tertiary hospital based cross-sectional study from Eastern India

Abstract: Context:Polycystic ovarian syndrome (PCOS), the most common endocrinopathy of women in the reproductive age group seems to be adversely affected by associated thyroid dysfunction. Both pose independent risks of ovarian failure and pregnancy related complications.Aims:The present study from Eastern India is, therefore, aimed to investigate the prevalence and etiology of different thyroid disorders in PCOS subjects.Settings and Design:Cross-sectional hospital based survey-single centre observational case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
110
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(135 citation statements)
references
References 17 publications
19
110
1
5
Order By: Relevance
“…Thyroid diseases and PCOS are two of the most common endocrine disorders in the general population. 8 Present results revealed a significant relationship between hypothyroidism and PCOS. Previous studies showed that there is a relationship between these two entities even though they have a complete different etiopathogenesis, yet both diseases share common clinical features.…”
Section: Pcos Was Originally Described In 1953 By Stein Andsupporting
confidence: 51%
“…Thyroid diseases and PCOS are two of the most common endocrine disorders in the general population. 8 Present results revealed a significant relationship between hypothyroidism and PCOS. Previous studies showed that there is a relationship between these two entities even though they have a complete different etiopathogenesis, yet both diseases share common clinical features.…”
Section: Pcos Was Originally Described In 1953 By Stein Andsupporting
confidence: 51%
“…Referring to the Colorado thyroid disease prevalence study, the prevalence of increased TSH levels in 24-year-old women should be revealed a higher prevalence of TPO-positive autoimmune thyroiditis than in 80 controls (22.5 vs 1.25%). PCOS patients had higher mean TSH levels, a higher prevalence of goiter (27.5 vs 7.5%), and more frequently a hypoechoic thyroid ultrasound pattern (12.5 vs 2.5%) than controls (22). Recently, a case-control Iranian study has demonstrated that, in PCOS patients, the mean level of TPO antibodies and the prevalence of clinically proven goiter were higher than those in controls without PCOS (23).…”
Section: Joint Prevalencementioning
confidence: 99%
“…Considering the study by Janssen et al (19), two patients with PCOS, but none of the controls, had been thyroidectomized because of Graves' disease. Additionally, two Indian patients with PCOS and no controls had Graves' disease (22).…”
Section: Joint Prevalencementioning
confidence: 99%
“…It has been shown that autoimmune thyroid diseases are more frequent in PCOS patients (39,40), but no difference in thyroid autoimmunity between PCOS patients and healthy controls was shown as well (41). Hyperestrogenism is thought to be responsible for more frequent autoimmune diseases in women compared to men (42).…”
Section: Discussionmentioning
confidence: 99%